P240 Pneumothorax management in cystic fibrosis patients. (2nd December 2011) - Gallagher, J; Chandramouli, S; Nazareth, D; Mohan, K; Ledson, M; Walshaw, M J; Greenwood, J
Abstract : Introduction: Spontaneous pneumothorax is a well-recognised complication in cystic fibrosis and is associated with increased morbidity and mortality. Although chemical pleurodesis and surgery are successful in preventing recurrence in non-CF patients, there are few data regarding their efficacy in CF. Method: To look at this further we reviewed the management and outcome of all 28 patients (mean age at first pneumothorax 26 years [range 18–54], mean FEV1 32% predicted [17–68], 18 female) in our centre who had developed a pneumothorax (58 episodes [1–7]) from 1993 to 2010. Results: Nine sustained bilateral pneumothoraces (either at initial presentation or as a subsequent event) and 16 recurrence (mean interval 4 months [1–12]). The outcomes of the initial and second line treatments are shown in the Abstract P240 table 1 . 14 patients (50%) died within 12 months and 20 (71%) within 2 years of their first pneumothorax, and five deaths occurred after surgery (mean 10 days [3–21]). The highest risk of recurrence occurred in the chest drain group (62%) followed by chemical pleurodesis (with 4 g talc) (57%), observation (40%) and the surgical group (20%). Conclusion: Thus, we have confirmed that spontaneous pneumothorax is a poor prognostic factor in CF, with 57% of patients experiencing a recurrent pneumothorax within the first year and poor one and 2-year survival rates. Surgical treatment was associated with a lower risk of recurrence, but at the expense of an increase in mortality. Randomised controlled trials of treatment options and the formulation of guidelines are required to determine the timing and optimal management to prevent recurrent pneumothorax in CF patients.